2015
DOI: 10.1037/a0037366
|View full text |Cite
|
Sign up to set email alerts
|

Prekindergarten children’s executive functioning skills and achievement gains: The utility of direct assessments and teacher ratings.

Abstract: An accumulating body of evidence suggests that young children who exhibit greater executive function ing (EF) skills in early childhood also achieve more academically. The goal of the present study was to examine the unique contributions of direct assessments and teacher ratings of children's EF skills at the beginning of prekindergarten (pre-k) to gains in academic achievement over the pre-k year. Data for the current study come from a subsample of children recruited for a large-scale pre-k curriculum interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
79
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 55 publications
6
79
1
1
Order By: Relevance
“…Similarly, Fuhs et al (2015) reported that an EF factor comprised of measures of inhibitory control, working memory, and shifting as well as a teacher-report of self-regulation uniquely predicted spring language, literacy, and mathematics scores after controlling for the corresponding fall score in a sample of 719 preschool children.…”
Section: Self-regulation and Academic Skillsmentioning
confidence: 92%
“…Similarly, Fuhs et al (2015) reported that an EF factor comprised of measures of inhibitory control, working memory, and shifting as well as a teacher-report of self-regulation uniquely predicted spring language, literacy, and mathematics scores after controlling for the corresponding fall score in a sample of 719 preschool children.…”
Section: Self-regulation and Academic Skillsmentioning
confidence: 92%
“…M. Allan, Allan, Lerner, Farrington, & Lonigan, 2015; Fuhs, Farran, & Nesbitt, 2015; Wiebe et al, 2011); however, some studies with preschool children report distinct IC and WM dimensions, depending on the tasks used and the ages of the children (e.g., Lerner & Lonigan, 2014; Schoemaker et al, 2012). There are a variety of tasks that can be used to measure EF, only some of which are appropriate for use with preschool-age children.…”
Section: Self-regulation Executive Function and Academic Achievementmentioning
confidence: 99%
“…However, a significant amount of research has demonstrated that several aspects of EF and self-regulation abilities are strongly correlated with academic achievement (e.g., Blair and Razza, 2007; Duncan et al, 2007; Li-Grining et al, 2010; Fuhs et al, 2014). It has been hypothesized that higher EF skills allow children to meet classroom demands quicker—i.e., those children have better attention capacities, memory of classroom rules, and are more capable to engage in academic content—which may enable them to benefit more from the academic environment that they are in Fuhs et al (2015) demonstrated that teachers' ratings as well as measurements of EF were directly correlated with academic achievement in prekindergarten children. Another study by Blair and Razza (2007) showed that teachers' ratings of effortful control and measurements of these EF skills were directly associated with children's literacy and mathematics skills during kindergarten.…”
Section: Introductionmentioning
confidence: 99%